Pengaruh Kreativitas Belajar, Kecerdasan Emosional, dan Perilaku Belajar Terhadap Tingkat Pemahaman Akuntansi Di Kota Batam - Agustina Agustina; Hermaya Ompusunggu (SEIKO : Journal of Management & Business, 2023)
A country's development and the rate of globalization are both significantly influenced by education. Education is the first step in the process of molding a person's personality, beliefs, and behaviors. College is the highest educational level available in Indonesia's public school system. This study aims to investigate the differences in learning creativity, learning behavior, and emotional intelligence among Batam City residents. 100 respondents who were accounting students enrolled in Pddikti's higher education in the seventh semester made up the sample for this study. utilizing the purposive sampling method to choose the sample. The information used in this study is primary data, namely information acquired via surveys provided to accounting major students. Data analysis employs IBM SPSS Statistics. The results and analysis of the study indicate that developing creativity, emotional intelligence, and behavior all have an impact on how effectively a person learns accounting. Keyword : The Learning Creativity, Emotional Intelligence, Learning Behavior, And Accounting Understanding.